Seeing the light : a mother's story - Simpson, Sharon (Blackburn, Victoria : PenFolk Publishing, 2016)
"When the primary school rang to say her youngest son had collapsed and was in a semi-convulsive state, Sharon's life was turned upside down ... she was struck with fear and paralysis. Why had this occurred to Jack? Why did Vincent escape? What does it mean for studies of identical twins when one so young is suddenly diagnosed with Juvenile MS? During the initial stages of Jack's illness Sharon experienced a near death experience and she became aware of something other than her own humanity. This awareness manifested as a light. The light centred round the visionary Australian Religious Sister Mary MacKillop and the extraordinary request from Jack to save himself..."--Back cover.
Keywords: Simpson, Sharon; Simpson, Jack; MacKillop, Mary, -- Saint -- 1842-1909; Critically ill children -- Australia -- Biography; Mothers -- Australia -- Biography; Mothers and sons -- Australia -- Biography; Miracles -- Australia -- Case studies; Trust in God -- Christianity -- Biography; Spiritual healing; Australian